LEGAL PROTECTION AGAINST USE RIGHTS TO COUNTERFEIT REGISTERED TRADEMARKS - Adil Dwi Laksono; Satino (RADJA PUBLIKA, 2025)
This study analyzes legal protection against the use of counterfeit trademark rights based on Law Number 20 of 2016 concerning Trademarks and Geographical Indications. Using a normative legal research method with a doctrinal juridical approach, the study analyzes primary and secondary legal materials related to trademark protection. The study results indicate that the legal protection framework includes preventive aspects through the trademark registration system and repressive aspects through civil lawsuit mechanisms, criminal sanctions, and alternative dispute resolution. Registered trademark owners are protected by exclusive rights that prevent the use of the trademark by other parties without permission, with criminal sanctions of up to 10 years in prison and a fine of IDR 5 billion for violators. Although the regulation is comprehensive, its implementation still faces significant challenges, especially related to the characteristics of complaint offenses that require reports from trademark owners as a prerequisite for law enforcement. Data on Indonesia's economic losses due to trademark counterfeiting, reaching IDR 291 trillion in 2020, indicates that the effectiveness of law enforcement is not yet optimal. The main challenges include the low legal awareness of business actors in registering trademarks, the complexity of proving violations in the digital realm, and the limited capacity of law enforcement officers to deal with increasingly sophisticated counterfeiting methods. This study concludes that a holistic strategy is needed to increase the effectiveness of brand protection, including intensive socialization, reform of complaint offense policies, simplification of registration procedures, strengthening of investigative capacity, and development of technology for early detection of violations.